Offenbarung und die Anökonomie der Tora: ein systematisch-theologischer Blick in die Talmudlesungen Emmanuel Levinas' - Ebert, Patrick (Etica & politica, 2021)
The following contribution deals with the question of a possible articulation of the connection between the soteriological and hamartiological dimension of the event of revelation in the JewishChristian tradition. In contrast to the classical Lutheran distinction between law and gospel, a proposal will be made instead, based on Levinas’ Talmud readings, as to how the connection between the soteriological and hamartiological dimensions of the event of revelation can be articulated in a systematic-theological way. For this purpose, Levinas’ elaboration on the connection between Tora and revelation as well as the motif of the ‘an-economy of the Tora’ will be taken into focus and supplemented by his phenomenological-philosophical writings, Derrida’s reflections on event and testimony and Bernhard Waldenfels’ reflections on a phenomenology of the alien.